Pengaruh Model Pembelajaran Project Based Learning terhadap Literasi Menulis Teks Laporan Hasil Observasi - Veronica Veronica; Liza Murniviyanti; Masnunah Masnunah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Observation Report Text is a text that contains a general description or reports something from observations. This studty was motivated by the low value of writing observation report text in junior high school students, this is caused by the lack of student interest in participating in learning caused by the inappropriate learning model so that student find it difficult to concentrate on learning. Based on this, the problem in this study is whether there is an Effect of the Project Based Learning Model on the Literacy Of Writing Observation Report Texts. The purpose of this study was to determine and describe the Project Based Learning Model on the Literacy of Writing Observation Report Text. The method used in this study was a quantitative experiment. The resuts of this study indicate that the Project Based Learning model is effective in improving the literacy of writing observation report texts in class VIII students of SMP Negeri 5 Penukal Utara. Therefore, the Project Based Learning model can be applied in learning Indonesian.